Validation of the Anti-Inflammatory Effect of Tenebrio Molitor Larva Oil in a Colitis Mouse Model - Park, B M; Lee, J; Jung, B G; Lee, B J (Folia biologica, 2022)
Ulcerative colitis is caused by various external factors and is an inflammatory disease that causes decreased intestinal function. Tenebrio molitor larvae contain more than 30 % fat, and the fat component consists of 45 % oleic acid, 20 % linoleic acid and 20 % polyunsaturated fatty acids. In this study, after administering Tenebrio molitor larva oil (TMLO) in a dextran sodium sulphate (DSS)-induced ulcerative colitis mouse model, the pathological findings and inflammatory markers of colitis were analysed to assess whether a colitis mitigation effect was achieved. In the TMLO-administered group, the colon length increased, the spleen weight decreased, and the body weight increased compared with that in the DSS group. In addition, the disease activity index level decreased, the mRNA expression level of inflammatory cytokines in the colon decreased, and the myeloperoxidase activity level significantly decreased. Also, the activity of the NF-κB pathway involved in the regulation of the inflammatory response was lower in the TMLO group than in the DSS group. Taken together, these results suggest that TMLO suppresses occurrence of acute ulcerative colitis in the DSS mouse model. Therefore, TMLO has the potential to be developed as a health food for the prevention and treatment of ulcerative colitis.
Keywords: Animals; antiflogistika; Tenebrio; Colitis, Ulcerative; Larva; síran dextranu; zvířata; Mice; Disease Models, Animal; modely nemocí na zvířatech; Dextran Sulfate; Anti-Inflammatory Agents; ulcerózní kolitida; Colitis; kolitida; larva; myši